Activity of trastuzumab-emtansine (TDM1) in HER2-positive breast cancer brain metastases: A case series. (2016) - Keith, Kevin C.; Lee, Yueh; Ewend, Matthew G.; Zagar, Timothy M.; Anders, Carey K.
Abstract: The incidence of breast cancer brain metastasis (BCBM) is increasing due in part to improved management of systemic disease and prolonged survival. Despite this growing population of patients, there exists little consensus for the treatment of HER2-positive BCBM. Lapatinib, the only brain permeable targeted agent for HER2-positive cancer, has demonstrated limited intracranial response rates and little improvement in progression free survival (PFS) for HER-2 positive patients. Size constraints are believed to prevent larger monoclonal antibodies, such as pertuzumab and trastuzumab, from crossing the blood brain barrier (BBB). However, emerging evidence reveals that the BBB is perturbed in the setting of metastases, allowing for improved penetrance of these larger targeted agents. The disrupted BBB may allow for passage of ado-trastuzumab emtansine (TDM1), though little clinical information about its activity in BCBM patients is currently known.